2001
DOI: 10.1105/tpc.010116
|View full text |Cite
|
Sign up to set email alerts
|

The PET1-CMS Mitochondrial Mutation in Sunflower Is Associated with Premature Programmed Cell Death and Cytochrome c Release

Abstract: In mammals, mitochondria have been shown to play a key intermediary role in apoptosis, a morphologically distinct form of programmed cell death (PCD), for example, through the release of cytochrome c , which activates a proteolytic enzyme cascade, resulting in specific nuclear DNA degradation and cell death. In plants, PCD is a feature of normal development, including the penultimate stage of anther development, leading to dehiscence and pollen release. However, there is little evidence that plant mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(63 citation statements)
references
References 64 publications
4
57
0
Order By: Relevance
“…It is already recognised that the decrease of MMP is an important mechanism associated with apoptosis in animal systems [23] and that cytochrome c release serves as a signal in several forms of programmed cell death in both animals and plants [4,24]. In our system, NO triggers a set of alterations typically associated with PCD as shown by nuclear condensation presented in Fig.…”
Section: Discussionmentioning
confidence: 68%
“…It is already recognised that the decrease of MMP is an important mechanism associated with apoptosis in animal systems [23] and that cytochrome c release serves as a signal in several forms of programmed cell death in both animals and plants [4,24]. In our system, NO triggers a set of alterations typically associated with PCD as shown by nuclear condensation presented in Fig.…”
Section: Discussionmentioning
confidence: 68%
“…An ultrastructural analysis, by Papini et al (1999), of the morphological events involved in tapetal cell death in Lobivia rauschii (a dicot) and Tillandsia albida (a moncot) demonstrated that death was accompanied by shrinkage of the whole cell and nucleus, condensation of the chromatin at the periphery of the internal nuclear membrane, enlargement of the endoplasmic reticulum (ER) cisternae, and persistence of the mitochondria and microfilament bundles, until the final stages of tapetal cell death. Similar morphological features occur during the premature cell death of anther tissues during cytoplasmic male sterile (CMS)-associated cell death in sunflower (Balk & Leaver, 2001). These authors also showed that the cells and nuclei condensed, and that nuclear DNA fragmented and was cleaved into oligonucleosomal units, yet the mitochondria persisted until extremely late in the cell-death process.…”
Section: Examples Of Apoptotic-like Morphologymentioning
confidence: 73%
“…Cytochrome c release has also been shown to occur during developmental cell death. In a study characterizing anther development in fertile and CMS sunflower, premature induction of PCD in the tapetum of CMS plants was found to be associated with release of cytochrome c from the mitochondria (Balk & Leaver, 2001). Release of cytochrome c was also found to be associated with death of poppy pollen tubes during self-incompatibility in Papaver pollen (Thomas & Franklin-Tong, 2004).…”
Section: Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…PCD in the plant and animal kingdoms share a number of morphological and biochemical features, including condensation and shrinkage of the nucleus and cytoplasm, DNA laddering and cytochrome c release from mitochondria (Danon et al, 2000;Balk and Leaver, 2001;Lam et al, 2001;Hoeberichts and Woltering, 2003). However, direct structural homologues of animal caspases with an analogous cleavage specificity and function have not been shown to exist in plants (reviewed by Bonneau et al, 2008).…”
Section: Introductionmentioning
confidence: 99%